Efecto antiinflamatorio del extracto hidroalcohólico de Oenothera rosea (Yawar Socco) en ratas con inducción a la inflamación aguda y crónica - Villena N, César A. (2012)
This present study of experimental design had as aim determines the anti-inflammatory effect of Oenothera rosea (Yawar socco) in rats which were induced acute and chronic inflammation. The whole plant was dried at 38 °C in an oven with circulating air, ground and macerated with a mix ethanol/water (70:30)1. It was used winter experimental model to evaluate the acute state (subplantar edema) induced with carrageenan and the model of xylene-induced edema ear. To determine the chronic inflammatory activity was used the model of carrageenan-induced granuloma using a modification of the technique described by Sedwick and Lees. It was used 132 albino rats of 300 g randomly divided in groups of eight each, one whereas a control with saline solution 5 mL/kg, one with the agent that induces inflammation (AI), AI groups and extract in 3 doses also with dexamethasone and ibuprofen, being 56 rats for evaluation against carrageenan where was considered milliliters of subplantar volume, percentage of anti-inflammatory efficacy, blood CRP level and histological examination of the inflammatory process, first in 56 to rats compared to Xylene expressing in mg of a piece of lobe. 50 mice were used to assess acute toxicity, 20 normal rats to see the effects of repeated doses in 28 days. Results showed a reduction of 60% acute inflammation (p <0.01) as well as 60% the chronic inflammation (p <0,05) and CRP was reduced by 45% (p < 0,03); there was no evidence of adverse effects, a 60% of anti-inflammatory effect in rats and 60% of chronic atrial edema effect, determining a MED of 61 mg/kg and no adverse effects. It’s concluded that under the experimental conditions it showed that hydroalcoholic extract of Oenothera rosea in rats has an antiinflammatory effect in rats has an antiinflammatory effect without hematologic and histopathological changes in rats.